Edukasi dan Pencegahan Gangguan Sendi Temporomandibular pada Kasus Kehilangan Gigi di Masyarakat Kecamatan Rappocini - Amirah Maritsa; Zahrawi Astrie Ahkam; Hasrini Hasrini; Aisyah AR; Zulkarnain Zulkarnain (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Tooth loss is an oral health problem that often causes disorders of the temporomandibular joint (TMJ), such as pain, clicking sounds, and difficulty chewing. This study aims to provide education and prevent TMJ disorders in the community of Rappocini District who experience tooth loss. The research method includes educational sessions through counseling and distribution of printed materials, as well as prevention through recommendations for the use of dentures and physical exercise. Evaluation was carried out by measuring changes in knowledge, attitudes, and symptoms of TMJ before and after the intervention. The results showed an increase in The research method includes educational sessions through counseling and distribution of printed materials, as well as prevention through recommendations for the use of dentures and physical exercise. Evaluation was carried out by measuring changes in knowledge, attitudes, and symptoms of TMJ before and after the intervention. Conclusion: The results of this study indicate that educational and clinical interventions can significantly improve the knowledge, attitudes, and behavior of diabetes mellitus patients towards their dental and oral health.